Short survival time following palliative‐intent hypofractionated radiotherapy for non‐resectable canine thyroid carcinoma: A retrospective analysis of 20 dogs. Issue 1 (4th September 2018) - Tsimbas, Kathleen; Turek, Michelle; Christensen, Neil; Vail, David M.; Forrest, Lisa
Abstract: Radiotherapy is the treatment of choice for non‐resectable canine thyroid carcinoma. High tumor response rates and median survival times of 2 years or longer have been previously reported with conventionally fractionated and hypofractionated protocols, even in dogs with distant metastasis. The objective of this retrospective, descriptive, case series study was to evaluate the clinical outcomes of dogs with thyroid carcinoma irradiated with palliative intent using hypofractionated radiotherapy at our institution. Medical records of 20 dogs treated between 1999 and 2014 were reviewed. All dogs had macroscopic primary tumors and presented with tumor‐related clinical signs. Median longest tumor diameter was 10 cm. Nineteen dogs (95%) had metastasis (7/19 lymph node; 16/19 distant metastasis). Most dogs were treated with four weekly fractions of 6.5–8 Gy. Radiotherapy was well tolerated in 17 dogs; three died of respiratory compromise before completing radiotherapy. Eleven dogs received adjuvant chemotherapy. Five dogs experienced a local tumor response including two complete and three partial responses. Overall median survival time was 170 days (range, 1–824 days; 95% CI: 58–392 days). Of potential variables examined (radiation delivery system and protocol, tumor size and location, vascular/lymphatic invasion, metastatic disease, chemotherapy, tumor response), only achievement of complete or partial response was predictive of overall survival. In contrast to previously reported cohorts, dogs with clinical signs and stage IV disease predominated in this study. Previous studies may over‐estimate survival following hypofractionated radiotherapy in dogs with advanced thyroid carcinoma.